Upport policy for public-private cooperation in science and technology in Vietnam - Nguyen Thi Minh Nga; Nguyen Thi Minh Hanh; Nguyen Thi Thuy Linh; Nguyen Thi Thu Huong; Dang Thi Thu Trang; Tran Minh Huyen (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2025)
Public-private cooperation in science and technology (S&T) is crucial for Vietnam's S&T policy development. The significance of such collaboration is supported by theoretical frameworks, international experiences, and Vietnam's practical activities. This article discusses the current state of policies supporting public-private cooperation in S&T in Vietnam and recommends necessary changes and improvements to enhance this collaboration in the future. Code: 24061001